Membangun Wawasan Global Warga Negara Muda melalui Pendidikan Kewarganegaraan Global di Indonesia - Aryanti Dwi Untari; Zaky Farid Luthfi; Ika Murtiningsih (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2024)
This article aims to describe the global insights of young citizens and the conceptual framework of global citizenship education in Indonesia. This study uses a descriptive qualitative approach with a literature study method carried out through several stages ranging from collecting, analyzing, to interpreting data from various written sources, such as books, journal articles, research reports, and other documents. Global insight includes not only knowledge of international events, but also an in-depth understanding of how those events are interrelated and impact everyday life in different parts of the world. In this era, young people must be able to think critically and be adaptive to global changes, as well as have high social awareness to be able to contribute positively in a global society. Global awareness includes cultural awareness, interconnectivity, global identity, social responsibility and critical thinking skills. All these dimensions aim to equip youth with the necessary skills to participate in a global society and deal with international issues. In the Indonesian curriculum, global citizenship education needs to be integrated with relevant approaches through thematic learning, collaborative projects, and the use of technology, aligned with the standards set by UNESCO to encourage awareness and active participation in global issues. This approach includes a number of key elements designed to improve learners' understanding, skills and attitudes in an interconnected global context.